Exploring causal relationships between immune cells and age-related macular degeneration through univariable, bidirectional, and multivariable Mendelian analysis - Wei, Xixiang; Yang, Hui; Yin, Xue; Fu, Zheng; Xiong, Weiwei (Frontiers in Medicine, 2024)
ObjectiveThis study systematically investigates the causal relationships between 731 immune cell phenotypes and age-related macular degeneration (AMD) using comprehensive Mendelian randomization (MR) analyses. The goal is to identify immune cell factors that contribute to or protect against AMD, thereby clarifying the immunological mechanisms underlying AMD pathophysiology and informing prevention and treatment strategies.MethodsUnivariable, bidirectional, and multivariable MR analyses were conducted to evaluate the associations between immune cells and AMD. By utilizing publicly available GWAS datasets, we eliminated the need for individual consents. The large-scale MR approach adhered to STROBE-MR guidelines. Immune cell GWAS data were sourced from a study involving 3,757 Sardinians, encompassing a broad spectrum of immune phenotypes, while AMD summary statistics were derived from a GWAS with over 3,763 cases. Instrumental variables (IVs) were carefully selected to comply with MR assumptions, and multiple MR methods were employed to enhance the robustness of causal inferences. Additionally, we supplemented the data for dry AMD (2,469 cases and 206,221 controls) and wet AMD (2,114 cases and 206,601 controls) for validation purposes.ResultsUnivariable MR analysis identified 17 immune cell phenotypes significantly associated with AMD, including 11 potential risk factors and 6 potential protective factors. Bidirectional MR analysis found no significant effects of AMD on the examined immune cell subsets. Multivariable MR analysis indicated that TD CD4+ %T cells and CD39+ CD8br %T cells likely inhibit AMD development, whereas CD39+ CD8br %CD8br cells and CD45RA on resting Treg cells appear to increase AMD risk. Validation of immune cell subsets in dry and wet AMD revealed significant associations between specific immune cells and both forms of AMD, with some subsets uniquely linked to wet AMD and others to dry AMD.ConclusionThis study addresses a critical gap in understanding the causal relationship between immune cells and AMD, identifying immune cell subsets that may either mitigate or exacerbate AMD risk. Notably, it highlights the potential role of CD39+ CD8+ T cells as anti-inflammatory agents and potential targets for immunotherapy in AMD. The absence of bidirectional causality suggests a complex origin of immune dysregulation in AMD. The differential associations of immune cell subsets with AMD subtypes carry significant implications for precision medicine approaches in ophthalmology, laying a solid foundation for future research focused on understanding the immunological underpinnings of AMD and developing targeted therapeutic strategies.